Online voting system using Blockchain (International Journal of Food and Nutritional Sciences, 2021)
Every individual in a democracy has the legal right to vote. Every person should have an equal opportunity to vote. EVMs and ballot papers are used to vote nowadays. The current voting method, on the other hand, has several severe flaws. We're working on an internet voting system that doesn't rely on electronic voting machines or ballot papers. Voting may be done quickly and easily online from any location. Blockchain is a cutting-edge technology that promises to improve electronic voting methods in general. In order to establish a feasible e-voting scheme, this initiative aims to showcase the most crucial elements of blockchain, such as cryptographic underpinnings and transparency. The proposed approach meets the basic requirements for systems of electronic voting while also providing end-to-end verifiability. The project shows how the multichain platform will be used to accomplish the anticipated e-voting system. It makes use of blockchain technology, which treats each vote as an irreversible transaction. Because the transactions are immutable, malicious attackers cannot alter them. This conclusion implies that this project has the potential to make voting more simple, fair, and accessible, and that it could be used as a future voting prototype.